Online Media to Address Violence against Women during COVID-19 Pandemic - Kristina Andryani; Felicciana Yayi Amanova; Rosalia Prismarini Nurdiarti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
This research aims to identify obstacles and analyze the strategic solution taken by the Public Relations of Rifka Annisa’s Women Crisis Center in utilizing online media platforms to address violence against women during the Covid-19 Pandemic in Yogyakarta. This research uses the qualitative case study method through observation and in-depth interviews at the Public Relations division of Rifka Annisa. Crisis Management and New Media concepts are used to analyze strategies in addressing the problem. The research results reveal that the outbreak of the Covid-19 pandemic has triggered the rise of violence against women. Social restriction during the pandemic is an obstacle for Rifka Annisa in reaching the violence victims and the wider community. Rifka Annisa shifts their usual face-to-face counseling programs for violence victims to online counseling programs. Similarly, they use online media platforms to advocate for public awareness, where they selectively select the online media type that suits the character of the target audience.